The Stretta Procedure Versus Proton Pump Inhibitors and Laparoscopic Nissen Fundoplication in the Management of Gastroesophageal Reflux Disease: A Cost-Effectiveness Analysis. (2008) - Comay, Dan; Adam, Viviane; da Silveira, Eduardo B; Kennedy, Wendy; Mayrand, Serge; Barkun, Alan N
Abstract : BACKGROUND: The Stretta procedure is an endoscopic therapy for gastroesophageal reflux disease. OBJECTIVE: To evaluate the cost-effectiveness of the Stretta procedure and that of competing strategies in the long-term management of gastroesophageal reflux disease. METHODS: A Markov model was designed to estimate costs and health outcomes in Canadian patients with gastroesophageal reflux disease over five years, from a Ministry of Health perspective. Strategies included the use of daily proton pump inhibitors (PPIs), laparoscopic Nissen fundoplication (LNF) and the Stretta procedure. Probabilities and utilities were derived from the literature. Costs are expressed in 2006 Canadian dollars. Units of effectiveness were symptom-free months (SFMs) and quality-adjusted life years (QALYs), using a five-year time horizon. RESULTS: In the analysis that used SFMs, the strategy using PPIs exhibited the lowest costs (40 per SFM) and the greatest number of SFMs, thus dominating both the LNF and Stretta systems. But the cost-effectiveness analysis using QALYs as the measure of effectiveness showed that PPIs presented the lowest cost-effectiveness ratio, while both the LNF and Stretta strategies were associated with very high incremental costs (approximately 353, 000 and 393, 000, respectively) to achieve an additional QALY. However, the PPI strategy did not dominate the two other strategies, which were associated with better effectiveness. CONCLUSIONS: If SFMs are used as the measure of effectiveness, PPIs dominate the Stretta and LNF strategies. However, if QALYs are used, the PPIs still present the lowest cost and LNF gives the best effectiveness. Regardless of the units of effectiveness or utility used in the present cost analysis, an approach of prescribing PPIs appears to be the preferred strategy.